Dielectric and polarization studies of magnetoelectric coupling in non-relaxor Pb(Fe1/2Ta1/2)O3 multiferroic ceramics. (12th March 2017) - Savinov, M.; Bednyakov, P.; Raevskaya, S. I.; Gusev, A. A.; Isupov, V. P.; Raevski, I. P.; Titov, V. V.; Chen, H.; Kovrigina, S. A.; Chou, C.-C.; Minasyan, T. A.; Malitskaya, M. A.
ABSTRACT: Dielectric permittivity ϵ and polarization / electric field hysteresis loops of highly-resistive Li-doped non-relaxor Pb(Fe1/2 Ta1/2 )O3 ceramics obtained by one-step sintering of the mechanically activated mixture of starting oxides and Li2 CO3 have been studied. Antiferromagnetic phase transition temperature TN ≈ 150 K was determined using Mossbauer spectroscopy studies at different temperatures. Though no anomalies in ϵ(T) curve at TN were observed, 1/ϵ(T) dependence exhibits change of the slope in the vicinity of TN . Anomalies in the temperature dependences of coercive field EC and derivative of the spontaneous polarization PS are observed near TN as well. These anomalies are attributed to magnetoelectric coupling.